2012
DOI: 10.1021/ie300107j
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Water Percolation Threshold of a Microemulsion Using Electrical Conductivity Measurements and Design of Experiments

Abstract: This paper presents the estimation of water percolation threshold (ϕ c ) of a nonionic microemulsion by studying its conductivity (σ) as a function of water volume fraction (ϕ). The initial solution of alkyl polyglycosides/glyceryl monooleate/ n-octane/isopropyl alcohol with weight ratios of 3/3/2/2 was diluted by brine (1 wt % sodium chroride), and the electrical conductance was measured along the specific dilution line. One factor design (OFD), which is an approach embedded in Design of Experiments (DOE), wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…The results obtained in this study for the dilution lines L1, L2, L3 and L4 ( Figure 6) indicate the presence of only one transition point corresponding to the transformation from w/o to water-continuous systems. Similar effects have been reported for other microemulsions [48][49][50].…”
Section: Conductivity Studiessupporting
confidence: 89%
“…The results obtained in this study for the dilution lines L1, L2, L3 and L4 ( Figure 6) indicate the presence of only one transition point corresponding to the transformation from w/o to water-continuous systems. Similar effects have been reported for other microemulsions [48][49][50].…”
Section: Conductivity Studiessupporting
confidence: 89%
“…The prepercolation exponent s is suggested to be near 1.00−1.20 and postpercolation exponent t be near 1.50 to 2.00, provided dynamic percolation dominates over static percolation in microemulsions. 40,43,52,56,57 We observed that the values of s, calculated for both the conductance and viscosity percolation, fit well within that range. The case of t is somewhat complicated, nevertheless; on one hand, the value calculated through fitting on eq 2 is anomalous to the suggested value ∼1.50−2.00.…”
Section: ■ Results and Discussionsupporting
confidence: 67%
“…The values of s and t, according to third degree polynomial fitting, have been 1.08 and 0.49, but the value for t optimized from fourth degree polynomial fitting has been 0.92. The pre-percolation exponent s is suggested to be near 1.00 to1.20 and post-percolation exponent t be near 1.50 to 2.00-provided dynamic percolation dominates over static percolation in microemulsions 40,43,52,56,57. …”
mentioning
confidence: 97%
“…The conductivity curves for m 1 / m 2 = (0.70:0.30, 0.60:0.40, and 0.50:0.50) exhibited a sigmoidal nature in their raising section, after the maximum, the conductance downward. These curves can be fitted fairly by eq (a Boltzmann equation, where w 0 is the center, κ takes on the average of κ i and κ f , d w 3 means the constant interval of w 3 , κ i and κ f are the initial and final conductances of the system, respectively). , The curves for m 1 / m 2 = (0.40:0.60, 0.30:0.70, 0.20:0.80, and 0.10:0.90) exhibit another nature which can be fitted fairly by eq (a polynomial equation, b 0 , b 1 , b 2 , b 3 are coefficients) . For K m = 0.33 and 0.25, the conductivity curves are shown in Figures a and a, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 The curves for m 1 /m 2 = (0.40:0.60, 0.30:0.70, 0.20:0.80, and 0.10:0.90) exhibit another nature which can be fitted fairly by eq 11 (a polynomial equation, b 0 , b 1 , b 2 , b 3 are coefficients). 28 For K m = 0.33 and 0.25, the conductivity curves are shown in Figures 5a and 6a, respectively. They are similar situations as Figure 4a as shown.…”
Section: ■ Results and Discussionmentioning
confidence: 99%